Fast motion estimation based on the special and temporal characteristic - Long LIU; Qi-jun SONG; Tai-fei ZHAO; Xiang-hui YUAN (Tongxin xuebao)
The spacial and temporal character of motion vector were analysed according to the spacial and temporal characteristic of motion vector,the different proposed search schemes were adopted for motion estimation;The experimental results shows the proposed algorithm reduce the prediction error and has a significant computational speedup compared with other algorithms,but offers a similar,even better performance.